Biomanufacturing of γ-linolenic acid-enriched galactosyldiacylglycerols: Challenges in microalgae and potential in oleaginous yeasts - Xiaosong Gu; Lei Huang; Jiazhang Lian (Synthetic and Systems Biotechnology, 2023)
γ-Linolenic acid-enriched galactosyldiacylglycerols (GDGs-GLA), as the natural form of γ-linolenic acid in microalgae, have a range of functional activities, including anti-inflammatory, antioxidant, and anti-allergic properties. The low abundance of microalgae and the structural stereoselectivity complexity impede microalgae extraction or chemical synthesis, resulting in a lack of supply of GDGs-GLA with a growing demand. At present, there is a growing interest in engineering oleaginous yeasts for mass production of GDGs-GLA based on their ability to utilize a variety of hydrophobic substrates and a high metabolic flux toward fatty acid and lipid (triacylglycerol, TAG) production. Here, we first introduce the GDGs-GLA biosynthetic pathway in microalgae and challenges in the engineering of the native host. Subsequently, we describe in detail the applications of oleaginous yeasts with Yarrowia lipolytica as the representative for GDGs-GLA biosynthesis, including the development of synthetic biology parts, gene editing tools, and metabolic engineering of lipid biosynthesis. Finally, we discuss the development trend of GDGs-GLA biosynthesis in Y. lipolytica.